Genetic Environments of blaCTX-M Genes Located on Conjugative Plasmids of Enterobacteriaceae Nosocomial Isolates Collected in Russia within 2003-2007 - N. K. Fursova; S. D. Pryamchuk; I. V. Abaev; YU. N. Kovalev; N. A. Shishkova; E. I. Pecherskikh; O. V. Korobova; E. I. Astashkin; D. M. Pachkunov; E. A. Svetoch; S. V. Sidorenko (Антибиотики и Химиотерапия, 2020)
The study showed that blaCTX-M genes were present in the genomes of 71% of сephаlosporin resistant Enterobacteriaceae nosocomial isolates (n=833) collected in Russian hospitals within 2003-2007, including 91% of E.coli, 90% of Klebsiella spp., 38% of Enterobacter spp., 31 % of Citrobacter spp. (n=9), and 36% of the other Enterobacteriaceae species. The genes belonging to the following subtypes (clusters) were identified: blaCΎX_M_1 (529 blaCTX_M_15 genes; 25 blaCTX_M_3 genes; 1 blaCTX_M_22 gene, 1 blaCTX-M-23 gene and 1 blaCTX-M-34 gene); blaCTX-M-2 (1 blaCTX-M-2 gene and 4 blaCTX-M-5 genes), and blaCTX-M-9 (2 blaCTX-M_9 genes, and 28 blaCTX_M_14 genes). It was shown that blaCTX-M genes were located on high-molecular weight (60-160 bp) conjugative plasmids belonging mainly to the incompatibility groups IncF, IncL/M and IncA/C (blaCTX-M-15 gene); IncL/M (blaCTX-M-3 gene); and IncF, IncL/M and IncIl-ly (CTX-M-14 gene). The gene environments of blaCTX-M genes were shown specific for the subtype of the genes. A mobile genetic element lSEcp1 (in some cases deleted or inserted by IS26, IS1, IS10, resTn2, or resTn3 sequences, in direct or reverse position) were detected upstream of blaCTX-M-3, blaCTX-M-14, and blaCTX-M-15 genes. A special characteristic was the sequence between ISEcpl and blaCTX-M gene: 48 bp for blaCTX-M-15 (except 1 E.coli isolate having such a sequence deleted by 3 bp); 127 bp for blaCTX-M-3; 42 bp for blaCTX-M-14. Downstream of blaCTX-M and blaCTX-M-15 genes in the major bacterial isolates orf477 mucA and Aorf477-AmucA sequences were detected respectively. Two isolates had additional Aorf3 insertion inside of Aorf477-AmucA sequence. Insertion sequence IS903 (intact or deleted) was detected downstream of blaCTX-M-14 gene. Unlike the others, blaCTX-M-2 and blaCTX-M-9 genes were located inside of IS CR1 mobile element, downstream of class 1 integron and orf513 sequence.